THE DETERMINANTS OF CLINICAL PRACTICE GUIDELINES UTILIZATION - Selahattin Akyüz; Yusuf Celik (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The aim is to reveal the effect of physicians' personality traits, attitudes towards Clinical Practice Guidelines (CPGs) and perceived barriers to use of CPGs on the use of CPGs. The data were obtained by a survey questionnaire from physicians working in a public hospital. The validity and reliability of scales was evaluated with factor analyzes and reliability coefficients. The relationships between independent variables that are physicians' personality traits, attitudes towards CPGs and perceived barriers to use of CPGs and dependent variables that is use of CPGs in practices were examined by correlation analysis. The effects of independent variables on the dependent variable were evaluated by regression analysis. Data collection tools used in the study were determined to be valid and reliable. It was determined that openness to experience and extroversion dimensions and positive attitude towards CPGs significantly affect the use of CPGs. It was also determined that the negative attitude towards CPGs and individual barriers to CPGs use had a significant and negative effect. It is evaluated that it may be beneficial to improve the physicians' positive personality traits, to increase their positive attitudes towards CPGs, to turn negative attitudes into positive and to make the necessary arrangements to eliminate the barriers to increase the use of the CPGs.